Birds - Henkes, Kevin; Dronzek, Laura ([New York] : Greenwillow Books, 2009)
Fascinated by the colors, shapes, sounds, and movements of the many different birds she sees through her window, a little girl is happy to discover that she and they have something in common.
2.1
K-3
Keywords: Birds -- Juvenile fiction; Birds -- Fiction; Birds -- Fiction